As the Den Burns : Poems - Rapier, Forrest (Book collections on Project MUSE., 2022)
"As the Den Burns is a debut collection that renders a sublime world on the verge of vanishing. Elegiac and surreal, primal and lyrical, these unpredictable poems vault from Tallahassee vigils to flooded gardens after a hurricane's landfall. Reading this collection is like swimming into the ocean; you float weightless amid waves of resistance, then knots form in your gut because something unseen moves beneath you. Mythology and song collide in this stunning collection as unruly poems waver from lifeguard chairs and cathedrals to lamps in underwater caverns. Rapier's poetry could be spray painted beneath a beach pier; every stanza shifts rapidly without apology, the shape of the words like a signature"--